(untitled) (ModaPalavra e-periódico, 2019)
This qualitative research aimed to ascertain the sustainability knowledge academic students of a Fashion design course possessed. The first researcher collected data during a pedagogical intervention, within the context of the product development discipline. Twenty third - year students from the above - mentioned course participated in the research and mobilized to respond to a questionnaire, present seminars and produce texts about sustainabi lity. The data analysis, collected through a questionnaire, the seminars videos and written texts, showed that the students, in addition to increasing their understanding about sustainability, reflected on its importance in the field of fashion, future work area of the researched students